LCA of Soybean Supply Chain Produced in the State of Pará, Located in the Brazilian Amazon Biome - Thyago Brito; Rui Fragoso; Pedro Marques; Anabela Fernandes-Silva; José Aranha (Biology and Life Sciences Forum, 2021)
Recently, Brazil became the biggest soybean producer and exporter in the world. The state of Pará, located in the Brazilian amazon biome, became one of the last agricultural frontiers of the country, which positively increased the soybean cultivation along it is territory. However, it is necessary to know the associated environmental impacts along the supply chain. Thus, we are applying the life cycle assessment (LCA) methodology using openLCA software to two producing regions: northeast pole (Paragominas) and south pole (Redenção). Based on the cradle to grave scope, the Recipe Midpoint (H) and Intergovernmental Panel on Climate Change (IPCC) methods of the environmental impact categories were used. To calculate the land use change (LUC), we used the BRLUC regionalized model (v1.3). The obtained results showed that LUC was mainly responsible for the global warming potential (GWP) along all soybean supply chains, especially when land occupied with tropical forests was adapted for growing soybeans. Despite the largest distance between the origin and destiny (road + railway = 1306 km), the soybean produced in the south pole (Redenção) is better shipped through the TEGRAM port of São Luis–Maranhão due to the use of multimodal platforms (lorry + train), allowing for a more efficient logistical performance (greater loads of grains transported and less environmental impact). The soybean produced in northeast pole (Paragominas) is better shipped through the ports around Barcarena–Pará due to the short distance by road (average 350 km) and hence less environment impact.